Pengaruh Good Corporate Governance terhadap Kecurangan Laporan Keuangan dengan Manajemen Laba sebagai Variabel Moderating - Triyani, Oetary; Kamaliah, Kamaliah; Azwir, Azwir (Jurnal Ekonomi, 2019)
This study aimed to determine: (1) the influence of Independent Commisioner on Fraudulent Financial Statement, (2) the influence of Audit Committee on Fraudulent Financial Statement, (3) the influence of Managerial Ownership on Fraudulent Financial Statement, (4) the influence of Institusional Ownership on Fraudulent Financial Statement, (5) the influence of Independent Commisioner, Audit Commitee, Managerial Ownership and Institusional Ownership on Fraudulent Financial Statement with earnings management as moderating variable. Population used in this study is manufacture company listed on BEI. The samples used purposive sampling, because observations obtained this study 132 (3 years. Data Analysis conducted by SPSS version 21.0. The result of this study is Independent Commisioner, Audit Commitee, Managerial Ownership and Institusional Ownership have influence to Fraudulent Financial Statement but not signifficant and Earnings Management become moderating variable between the Independent Commisioner, Audit Commitee, Managerial Ownership and Institusional Owenership to Fraudulent Financial Statements, but not signifikan too.